Features of Investment Activity Management in the Mineral and Raw Materials Sector of the Economy - SIKHIMBAYEV, Muratbay; SHUGAIPOVA, Zhanna (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The research considers the mineral and raw materials sector of the Republic of Kazakhstan for the years of independence, the special features of the management system of investment activity in the mineral and raw materials sector of the economy of the Republic of Kazakhstan, attraction of foreign investments. One of the most important areas for attracting investments in Kazakhstan is the mineral and raw materials complex, at the same time, today it is necessary to attract investments not only to finance finished mining projects, but also to form complex high-tech industries that ensure effective exploration and exploration of new deposits, complex enrichment of raw materials and high conversion goods production. In general, the comprehensive development of Kazakhstan's mineral resource base implies a critical review of regional mineralogical concepts, the development and implementation of new methods for forecasting, prospecting and evaluation of deposits, the study of the factors of the formation of deposits, the solution of technological and geo-ecological aspects of development of deposits and, of course, ensuring sufficient funding for all these activities.